Virginity Reflected in Ayu Utami's Saman Novel (1998): A Feminist Approach - Mulyani, Sri; , Dewi Candraningrum, Ph.D (2017)
This research aims to analyze the virginity every character telling their sexual experiences in their own way, too vulgar, reflected on Ayu Utami's Saman Novel, the purpose of the research is reveal what is virginity and how is virginity reflected in Ayu Utami's novel using a Feminist Approach. The type of this research is qualitative research. The researcher took the data from the novel include the narration, monologue, and dialogue. The techniques of collecting the data is using library research, and the technique of the data analysis is using descriptive analysis which firstly, the writer reads and comprehends the primary and secondary data source, notes down of important information in both sources, selects them by accepting the relevant information with the problem and rejecting the irrelevant information that does not support the topic of the study. Beside that the writer uses internet to find the information about the novel and literary theory that she uses. Problem statement of the research is how Ayu Utami describes the virginity through Saman novel. The first is based on the analysis of structural elements, and the second is the analysis of virginity by using the theory of feminism and the result of this research shows The first is a novel structural element obtained through the characters and characterization, setting the place and time, plot, point of view, and the theme is structured into one as the story in the novel. The second is based on the theory of feminism in the participation of women, the role of women, women's rights, and the position of women that occurred on the main character and the other characters in the Saman novel (1998). Keyword: Virginity, structural element of novel, feminist approach